Community Empowerment by Utilizing Village Potentials Towards a CEMARA Community (Smart, Independent, and Prosperous) During the Covid-19 Pandemic in Kaban Tua Village, Munte District, Karo Regency - Daulay, Wardiyah; Nasution, Mahnum Lailan; Wahyuni, Sri Eka (Talenta Publisher, 2020)
The level of transmission of Covid-19, which is still quite high, is a concern for immediate efforts that can help people avoid Covid-19. Problems found in Kaban Village are still many children who do not wear masks and continue to play freely without paying attention to the covid-19 protocol, disruption of teaching and learning activities so that children are left behind in lessons, facilities for washing hands are not yet available. This activity aims to train and educate the public to continue to equip themselves and fill useful free time during the COVID-19 pandemic in Kaban Tua Village, Munte District, Karo, North Sumatra. This activity is carried out in four forms of activities which include counseling and distribution of masks / handsanitizers, education on washing hands with soap, education and recitation activities for children. The results achieved from this service activity are (1) increased public insight and knowledge about the discipline of the Covid-19 health protocol, (2) the community has cloth masks and handsanitizers as personal protective equipment, (3) children are not left behind in learning materials at school and continue to carry out Koran activities, and (4) increased public awareness to invite other people and wear masks to protect themselves from Covid-19 transmission. This program is expected to be sustainable and provide many benefits so that people can avoid the transmission of Covid-19.